Positive youth development through sport: A narrative review - Burhan Hambali; Amung Ma'mun; Budi Susetyo; Yusuf Hidayat (Universitas Pendidikan Indonesia, 2022)
The global issue of the importance of positive youth development has become an interesting topic to be studied more deeply. This is evidenced by the number of research results discussing positive youth development (PYD) in the sports context. This research generally aimed to examine the critical role of sport in forming PYD through the study on the research result development from time to time and strengthen the results of previous studies. The research was conducted using a literature review method with the narrative type. The article search was conducted to identify PYD through sports research results. The publication period of articles was quoted from 2000 to 2019. Database search was conducted through Google Scholar, Tailor and Francis, Elsevier, Science Direct, and Sage using positive youth development and development through sports keywords. All articles found as primary data were analyzed using critical appraisal analysis techniques, namely the process of analyzing relevant articles related to the results and theoretical basis being studied. The analysis and synthesis results show that sports, in general, can develop positive youth development, such as physical fitness development, social development, and life skill development, as the benchmarks for the country's success with youth as agents of change in the future. Therefore, it is important for a country to use sport to develop positive youth through sports activities.